2020
DOI: 10.1093/cdn/nzaa140
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Child and Parent Knowledge of Added Sugar Recommendations and Added Sugar Intake in Multiethnic Elementary-Aged Children

Abstract: Background A key goal of the Dietary Guidelines for Americans 2015–2020 is to reduce added sugar intake by increasing public knowledge about added sugars. However, research has not shown if knowledge of added sugar recommendations is associated with intake. Objective To determine the relationship between parent and child knowledge of added sugar recommendations on added sugar intake in primarily low-income and Hispanic 3rd to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…These results were consistent with previous findings of a cross-sectional study that examined the probability of obesity with higher sweets and sugar intakes in a national representative sample of 781 children and 384 adolescents in Greece, indicating that most of the participants exceeded the recommended intake of sweets and sugar-sweetened beverages (39) . Similar results were also observed in a cross-sectional study of 109 children in Ontario, in which 80 % of children had intakes of free sugar greater than the recommended intake (40) . In support of this, recent systematic review evaluating the world dietary sugar intake trends in children and adolescents reported that the sugar intakes as a percentage of total energy are the highest for children and adolescents, and despite some reductions in sugar intake observed in a few individual studies, overall intakes of sugars remain above recommendations (41) .…”
Section: Discussionsupporting
confidence: 83%
“…These results were consistent with previous findings of a cross-sectional study that examined the probability of obesity with higher sweets and sugar intakes in a national representative sample of 781 children and 384 adolescents in Greece, indicating that most of the participants exceeded the recommended intake of sweets and sugar-sweetened beverages (39) . Similar results were also observed in a cross-sectional study of 109 children in Ontario, in which 80 % of children had intakes of free sugar greater than the recommended intake (40) . In support of this, recent systematic review evaluating the world dietary sugar intake trends in children and adolescents reported that the sugar intakes as a percentage of total energy are the highest for children and adolescents, and despite some reductions in sugar intake observed in a few individual studies, overall intakes of sugars remain above recommendations (41) .…”
Section: Discussionsupporting
confidence: 83%
“…This study is one of the few to examine knowledge about sugar sources and guidelines to reduce sugar intake (see also, [ 20 , 53 , 54 ]) and, to the best of our knowledge, the first one to be conducted with a Portuguese sample. Most participants in this study experienced difficulties in categorizing sugar sources and seemed to be unaware of the WHO’s guidelines for reducing sugar intake.…”
Section: Discussionmentioning
confidence: 99%